Short- and long-term effects of assessment-based differentiated reading instruction in general education on reading fluency and reading comprehension. (August 2018) - Förster, Natalie; Kawohl, Elisabeth; Souvignier, Elmar
Abstract: Studies on Child x Instruction interactions show that learning growth depends on the fit of instruction to students' abilities. This study investigates short- and long-term effects of combining learning progress assessment (LPA) as a tool for teachers to constantly monitor their students' progress with differentiated reading instruction to address students' individual needs on reading fluency and reading comprehension. The study was conducted in German elementary school classrooms. Third grade classrooms ( n = 28) were randomly assigned to either an LPA group with differentiated instruction or a control group (CG). Students in the treatment group showed higher growth in reading fluency than students in the CG ( d = .30). The effect was stable over the two-year period of the study. Students with lower reading skills benefited more from the treatment. No effects were found on reading comprehension. Results are discussed with regard to teachers' use of data to differentiate instruction. Highlights: Assessment-based reading instruction could be successfully implemented in general education. Assessment-based reading instruction effected higher growth in reading fluency but not in reading comprehension. This effect was stable over a two year period. Students with lower reading skills benefited more from the treatment. Results underline Child x Instruction interactions.